NUMERICAL INVESTIGATION OF COMPOSITES FOR RADAR ABSORBING MATERIALS USING WAVEGUIDE METHODS. - Anggita Chandra Aisyah, Dania
Stealth technology on fighter aircraft uses the combination of radar absorption material (RAM) and geometry to minimize the reflection of electromagnetic waves back into the radar system. Currently, carbon-based polymer composites are widely researched and developed as RAM because of their high flexibility in design and control properties. The composite material must be strong and light and capable of providing stealth properties to military aircraft for infiltration missions. One of the very important properties of stealth technology applications is the radiation absorption property of composite materials; this is very important to be tested before it can be implemented on fighter aircraft. In this final project, a parametric study will be conducted to determine what factors affect the characteristics of RAM made of composite materials using numerical simulation. Numerical simulations were performed using the Altair FEKO software. The value of the S parameter of the composite material obtained from the numerical simulation is then compared with the results obtained from the experiment using the rectangular waveguide method. The parameters studied and varied were the number of meshing and permittivity, which were then seen to affect the radiation absorption properties. Based on the simulations carried out in this study, it was found that the meshing size does not affect the radiation absorption properties, while permittivity plays a large role in varying the radiation absorption value